The effectiveness of tax credits as a policy tool to promote R & D activity: a systematic review and meta-regression analysis - Yang, I-Hua (Auckland University of Technology, 2011)
Endogenous technical progress is a hall mark of endogenous growth theory which aims to provide an endogenous explanation of technological progress and economic growth within a general equilibrium framework. A principal claim to originality is that endogenous growth theory can accommodate increasing returns, and knowledge is accorded a central role in the explanation of modern technical progress and growth dynamics. To stimulate research and development (R & D) activity, governments have promoted a range of policies but principally through tax credits. However, promoting R & D activity through tax incentives is not well supported in the economics literature. Moreover, empirical studies evaluating the relationship between R & D activity and tax credits have provided mixed results which motivate this study. Meta-regression analysis (MRA) is a form of meta-analysis and used to investigate whether study characteristics may explain heterogeneity of results among studies in a systematic review. Although researchers in psychology, education, and the health sciences have used MRA extensively, it has been little used by economists. This study performs MRA to investigate the relationship between tax credits and R & D activity; drawing data from 21 papers yielding 124 estimated effects. Information collected on each estimate allows us to test my main hypotheses; that a tax credit will lead to higher levels of R & D than without the credit, and further find out which specific policy differences have the most important impacts on estimated tax credit effects. The results of the MRA generally confirm the effect of tax credits on R & D activity among positive and negative measures of tax credits as the analysis only considers data characteristics as moderator variables. However, the interesting finding is that the estimated impact of tax credits on R & D activity is statistically negative under all measures and types of tax credit. In addition, there is evidence that inflation and macroeconomic shocks have a relatively strong influence over the effectiveness of R & D tax credits. These findings represent a challenge for those who believe that tax credits have stimulated R & D activity. Thus, this analysis suggests that the research design and data choices are crucial for any accurate analysis of the impact of R & D tax credits on R & D activity.
Keywords: Tax credits; R & D; Meta-regression